Minimum wage and informality in Ecuador - Carla Canelas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper investigates if changes in the minimum wage have influenced changes on the formality and informality rates, and the level of wages in Ecuador. A 12-year panel was built. It allows to overcome the short time span of household data and so to characterize changes over time. Results suggest that the minimum wage has virtually no effect on employment and wages. The high level of non-compliance, and the important share of informal workers call for new policies and institutions concerned with the enforcement of labor regulations and design of social security systems and laws that protect informal workers.
Keywords: J21; J23; J3; 330; labor markets; informality; minimum wage